Micronutrient Management and Health Impacts in the Elderly: Literature Review - Inayatul Fitri (Professorline, 2024)
The elderly are an age group that is vulnerable to experiencing micronutrient problems, which can have a significant impact on their health and quality of life. This literature review aims to examine micronutrient management in the elderly and its impact on health. The method used was a literature search from various electronic databases, including research articles and systematic reviews published in the last 10 years. The results of the review show that micronutrient deficiencies are common in the elderly, especially vitamin D, vitamin B12, iron, and calcium. Contributing factors include decreased food intake, age-related physiological changes, drug interactions, and chronic health conditions. Effective micronutrient management includes regular nutritional status assessments, dietary interventions, appropriate supplementation, and nutritional education. The health impacts of micronutrient deficiencies in the elderly are very diverse, including an increased risk of osteoporosis, anemia, cognitive impairment, depression, and decreased immune function. Conversely, optimal micronutrient management can improve bone health, cognitive function, immune system, and cardiovascular health. This review also identified several challenges in micronutrient management in the elderly, including adherence to supplementation, variations in individual needs, and the complexity of interactions between various micronutrients. Suggested strategies include personalized approaches in nutritional interventions, integration of micronutrient management into primary health care, and increased awareness of the importance of micronutrients among health professionals and the general public. Effective micronutrient management has an important role in improving the health and quality of life of the elderly. Further research is needed to optimize intervention strategies and overcome challenges in their implementation.